THE USE OF SHORT ANIMATED MOVIE TO IMPROVE STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXT - Rusli Irawan (Didascein : Journal of English Education, 2023)
The appropriate and effective media that will be able to attract the students’ interest is the short animated movie that could help students improve writing skill. Thus, the objective of this study was about to find out whether it is effective to use short animated movie to improve students’ skill in writing descriptive text to the seventh-grade students of Sumsel Jaya Junior High School Palembang or not. The experimental method was used in this study whereas the design of this method was using pre-experimental design. The type of the experimental design used was one group pretest-posttest design. The population of this study was 62 students  and 30 students as the sample, which chosen through convenience non-probability sampling. The format of the test was essay and the test was using two raters to check the test result. The data obtained was analyzed by using matched t-test. It was supported by the result of the data analysis where the t-obtained that the result of matched t-test calculation was 9.427. It was higher than critical value 1.699. It could be concluded that the use of short animated movie to improve students’ skill in writing descriptive text to the seventh grade students of Sumsel Jaya Junior High School was effective.